IMMUNOLOGICAL COMPLEXITY AND SEPSIS-RELATED GRAFT DYSFUNCTION IN A PEDIATRIC KIDNEY TRANSPLANT RECIPIENT: A CASE-BASED REVIEW - Вакуленко, Л.І.; Оболонська, О.Ю.; Реніта, Раджкумар; Медведська, О.В. (SWorldJournal, 2025)
Pediatric kidney transplantation is a definitive therapeutic intervention for end-stage renal disease, significantly improving both survival and quality of life. However, the procedure comes with unique challenges, primarily due to a child’s still-develop